Lysate of probiotic Lactobacillus casei DN-114 001 ameliorates colitis by strengthening the gut barrier function and changing the gut microenvironment - Zakostelska, Zuzana; Kverka, Miloslav; Klimesova, Klara; Rossmann, Pavel; Mrazek, Jakub; Kopecny, Jan; Hornova, Michaela; Srutkova, Dagmar; Hudcovic, Tomas; Ridl, Jakub; Tlaskalova-Hogenova, Helena (PloS one, 2011)
BACKGROUND: Probiotic bacteria can be used for the prevention and treatment of human inflammatory diseases including inflammatory bowel diseases (IBD). However, the nature of active components and exact mechanisms of this beneficial effects have not been fully elucidated. Our aim was to investigate if lysate of probiotic bacterium L. casei DN-114 001 (Lc) could decrease the severity of intestinal inflammation in a murine model of IBD. METHODOLOGY/PRINCIPAL FINDINGS: The preventive effect of oral administration of Lc significantly reduces the severity of acute dextran sulfate sodium (DSS) colitis in BALB/c but not in SCID mice. In order to analyze how this beneficial effect interferes with well-known phases of intestinal inflammation pathogenesis in vivo and in vitro, we evaluated intestinal permeability using the FITC-labeled dextran method and analysed tight junction proteins expression by immunofluorescence and PCR. We also measured CD4(+)FoxP3(+) regulatory T cells proportion by FACS analysis, microbiota composition by pyrosequencing, and local cytokine production by ELISA. Lc leads to a significant protection against increased intestinal permeability and barrier dysfunction shown by preserved ZO-1 expression. We found that the Lc treatment increases the numbers of CD4(+)FoxP3(+) regulatory T cells in mesenteric lymph nodes (MLN), decreases production of pro-inflammatory cytokines TNF-α and IFN-γ, and anti-inflammatory IL-10 in Peyer's patches and large intestine, and changes the gut microbiota composition. Moreover, Lc treatment prevents lipopolysaccharide-induced TNF-α expression in RAW 264.7 cell line by down-regulating the NF-κB signaling pathway. CONCLUSION/SIGNIFICANCE: Our study provided evidence that even non-living probiotic bacteria can prevent the development of severe forms of intestinal inflammation by strengthening the integrity of intestinal barrier and modulation of gut microenvironment.
Keywords: down regulace; Administration, Oral; permeabilita; imunita; metagenom; Lipopolysaccharides; Tumor Necrosis Factor-alpha; Mice, SCID; lipopolysacharidy; probiotika; regulační T-lymfocyty; membránové proteiny; Colitis; Digestive System; aplikace orální; Membrane Proteins; myši inbrední BALB C; počet lymfocytů; střevní sliznice; fosfoproteiny; Lacticaseibacillus casei; Phosphoproteins; Macrophage Activation; aktivace makrofágů; Mice, Inbred BALB C; Permeability; akutní nemoc; Acute Disease; T-Lymphocytes, Regulatory; Lymphocyte Count; Metagenome; Animals; Down-Regulation; lidé; Lactobacillus casei; Zonula Occludens-1 Protein; ženské pohlaví; Humans; zvířata; myši SCID; NF-kappa B; Intestinal Mucosa; myši; Probiotics; TNF-alfa; Immunity; kolitida; Mice; Female; protein zonula occludens 1; trávicí systém